(3OhGhjf GdTYQGA GdLGgdjjfs - (3eLehYI TYQGAs ((3YeQ Hf QeVGf GdgjJej s)
(3ChdgG (B:s
(3bGd Wajd Hf Yha GdZfhj(B: (3hHGdb`a`Q OGQ ef LejdI gjLJ ShGda MH aj aDGOj defUH s
(3BNQgG (B:s
(3ef TYQ YfJQI bhdg(B: (3hcGf aJi GdgjLGA jMej PeGQgG hjVQH YfO GdcQ cd HfGf s
(3HgG GVWQGH aj HYV ChQGbgG HOkA ef U (B40 (3hQHeG cGf gPG GdecGf Chd GdcJGH Ch CfgeG cJGHGf eNJdaGfs
(3aj Chd GdfSNI h hSWgG JedjcGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B9 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdYQGbj HHZOGO (B(1469) s
Keywords: (3GdCOHs